ANALISIS SWOT, ANALYTICAL HIEARCHY PROCESS, DAN TECHNIQUE FOR OREDE PREFERENCE BY SIMILARITY TO IDEAL SOLUTION PADA STRATEGI PENGEMBANGAN USAHA KERUPUK IKAN PASCA PANDEMI COVID-19 (STUDI KASUS: UMKM PUJI RAHAYU REMBANG) - Indira Asri, Vikha; Rizal Febrianto, Bagus; Sokhibi, Akh. (Journal of Industrial Engineering and Technology, 2023)
Fish crackers are one of the superior regional products of Rembang Regency, which are produced by several MSMEs in the Rembang Regency area. Puji Rahayu is one of the SMEs that produces fish crackers. After the Covid-19 pandemic, these MSMEs experienced a decline in terms of product sales. Therefore this study aims to determine the business development strategy of the Puji Rahayu Fish Cracker MSME business in Rembang Regency. This study uses several methods in processing data, so that it can determine the right method with a higher level of accuracy. To determine the development strategy using SWOT analysis while the many criteria used in the MSME development strategy were solved by Multi Criteria Decision Making (MCDM) using the AHP and TOPSIS methods. The results of the analysis show that there are three priority alternatives for Puji Rahayu's MSME business development strategy with the highest priority being product diversification in terms of taste and product packaging with a weight of 0.296, improving production quality with a weight of 0.273, and utilizing appropriate technology to optimize MSME performance results with a weight of 0.238 . The alternative strategy that is a top priority in developing Puji Rahayu's MSME is to improve production quality by improving product quality by controlling the production process well, so that it will produce products that have good quality.